2020
DOI: 10.32865/fire202063225
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationships between Possible Selves and Early Teacher Identity of Turkish Pre-service Teachers

Abstract: Pre-service teacher (PST) education at higher education institutions is pivotal to early teacher identity development. Possible selves theory presents a framework for understanding teacher professional identity, which is theoretically supported but not empirically tested sufficiently. This study set out to examine PSTs’ early teacher identity in the Turkish context and the expected and feared possible selves of PSTs as predictors of early teacher identity through structural equation modeling based on empirical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
2
11
0
4
Order By: Relevance
“…Results indicated that preservice elementary teachers held a high level of perception of professional identity. This finding is congruent with the previous literature indicating positive perceptions of preservice teachers regarding themselves as teachers (Eğmir & Çelik, 2019;Erdem, 2020;Kavrayıcı, 2020). The present study also revealed that preservice elementary teachers' perceptions of professional identity were not significantly different based on the universities they attended.…”
Section: Extended Abstractsupporting
confidence: 91%
See 2 more Smart Citations
“…Results indicated that preservice elementary teachers held a high level of perception of professional identity. This finding is congruent with the previous literature indicating positive perceptions of preservice teachers regarding themselves as teachers (Eğmir & Çelik, 2019;Erdem, 2020;Kavrayıcı, 2020). The present study also revealed that preservice elementary teachers' perceptions of professional identity were not significantly different based on the universities they attended.…”
Section: Extended Abstractsupporting
confidence: 91%
“…Obtaining this finding might be related to having different participants at different grade levels. A study conducted by Erdem (2020) supports this finding by revealing a non-significant difference between freshmen and senior preservice teachers with respect to teacher identity. However, Eğmir and Çelik (2019) found that senior preservice teachers' professional identity was higher than the early graders'.…”
Section: Extended Abstractmentioning
confidence: 80%
See 1 more Smart Citation
“…Bu bulgu öğretmen adaylarının meslek öncesi öğretmen kimliği algılarının ortalamanın üstünde ve yüksek düzeyde olduğunu göstermektedir. Benzer çalışmalarda da öğretmen adaylarının erken öğretmen kimlik algılarının yüksek düzeyde olduğu belirlenmiştir (Babanoğlu ve Ağçam, 2019;Çelik ve Kalkan, 2019;Eğmir ve Çelik, 2019;Erdem, 2020b). Pedagojik formasyon programındaki öğrencilerin de erken öğretmen kimliği düzeylerinin yüksek düzeyde olduğu belirlenmiştir (Ulubey, Yıldırım ve Alpaslan, 2018).…”
Section: Dördüncü Araştırma Sorusuna İlişkin Bulgularunclassified
“…Marcus ve Nurius tarafından geliştirilen Olası Benlikler Kuramı'nın, kimlik gelişimini incelemeye yönelik gerçekleştirilen araştırmalarda sıklıkla kullanıldığı dikkat çekmektedir. Bu araştırmaların önemli bir kısmının öğretmen adayları (Hamman, Wang ve Burley, 2013;Al-Khairi, 2015;Dalioğlu ve Adıgüzel, 2015;Dalioğlu ve Adıgüzel, 2017;Babanoğlu, 2017;Babanoğlu ve Ağçam, 2018;Çetin ve Eren, 2019;Eren ve Yeşilbursa, 2019;Gün ve Turabik, 2019;Ölçer, 2019;Çağlar vd., 2020;Erdem, 2020;Tabak vd., 2020), öğretmen adayı ve öğretmenler (karma) (Hamman vd., 2010;Mahmoudi-Gahrounei vd., 2016) ve öğretmenler (Karimi ve Norouzi, 2019) üzerinde gerçekleştirildiği ve büyük araştırma grupları üzerinde yürütüldüğü görülmektedir.…”
Section: Kavramsal çErçeveunclassified